The Influence of Motivation and Work Discipline in Improving Employee Performance of CV. BOSS Sukses Sejati Makassar - TN, Asriana (Generasi Sains Indonesia, 2024)
A quantitative study, which was carried out in the framework of CV. BOSS Sukses Sejati Makassar researched on how highly motivation and work discipline were in predicting employee performance. The correlational research design was used, and 100 participants were recruited in the study consisting of heterogeneous organizational segments and measuring dependent variables, motivation and work discipline, with standardized questionnaires, supplemented by supervisor-rated and self-evaluated performance scores obtained in corporate records. There were several regressions showing that motivation and work discipline had a significant effect on output and that the influence of work discipline was significantly greater compared to motivational influence. These findings imply that organizational norms, being prompt, and doing everything by the book are more determinant of employee performance than more individualistic (motivating) aspects. Therefore, as much as motivation is a non-negotiable element that drives goal achievement, cultivated behavior provides them with the uniformity and reliability that anchors performance. These results highlight the two-fold strategic necessity of work discipline and high motivation intertwining. Managerial interventions must therefore promote a working culture that blends the importance of psychological motivation-appreciation and career growth and behavioral models that advance responsibility and standardization of processes. Based on such balancing, organizations make their expected behavior more aligned with the achieved performance and vice versa, maximizing productivity.